A cross sectional study of tobacco use among the college students of B. G. Nagara, Karnataka - Raja, N. Sabari (International Journal Of Community Medicine And Public Health, 2019)
Background: Tobacco is a leafy plant grown around the world with its addictive substance nicotine. It becomes the need of the hour to provide enough evidence on the correlates of tobacco use in the community to assist government policy makers, health professionals and the public in developing realistic models towards effective tobacco control to cater to sections of community in need. The present study was conducted to determine the prevalence and the pattern of tobacco use among the college students and to find out the reasons for the tobacco use among the college students. Methods: A descriptive cross sectional study was conducted among various college students of B. G. Nagara with 1003 subjects selected. Data was collected with a pre-tested, semi-structured questionnaire and analysed. Results were expressed in percentages and proportions. Results: The overall prevalence of tobacco use among the study subjects was found to be 5.8% and was exclusively among male students only. Cigarette smoking was the most commonly used form of tobacco, used by 89.7% of the tobacco users and the major reasons for initiation of tobacco use were due to friends (58.6%). Conclusions: Present study showed that the prevalence of tobacco use (5.8%) was lower when compared to state and national average. But since majority of users were in the age group of 19 to 21 years and were away from their homes, strict measures should be enforced in hostel and college premises banning its use and sale.